Directing clinical care using lower extremity biomechanics in patients with ankle osteoarthritis and ankle arthroplasty. Issue 11 (16th June 2017) - Queen, Robin
ABSTRACT: Ankle osteoarthritis is a debilitating disease with approximately 50, 000 new cases per year leading to skeletal deformity, severe and recurrent pain, cartilage breakdown, and gait dysfunction limiting patient mobility and well‐being. Although many treatments (total ankle arthroplasty [TAA], ankle fusion [arthrodesis], and ankle distraction arthroplasty) relieve pain, it is not clear that these procedures significantly improve patient mobility. The goal of the research presented here is to summarize what is presently known about lower extremity gait mechanics and outcomes and to quantify the impact of ankle osteoarthritis and TAA have on these measures using an explicitly holistic and mechanistic approach. Our recent studies have explored physical performance and energy recovery and revealed unexpected patterns and sequelae to treatment including incomplete restoration of gait function. These studies demonstrated for the first time the extreme levels and range of gait and balance dysfunction present in ankle osteoarthritis patients as well as quantifying the ways in which the affected joint alters movement and loading patterns not just in the painful joint, but throughout both the ipsilateral and contralateral lower extremity. Through this work, we determined that relieving pain alone through TAA is not enough to restore normal walking mechanics and balance due to underlying causes including limited ankle range of motion and balance deficits leading to long‐term disability despite treatment. The results indicate the need to consider additional therapeutic interventions aimed at restoring balance, ankle range of motion, and movement symmetry in order to improve long‐term health and function. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2345–2355, 2017.